Training on Speech Techniques Using Malay and Indonesian at the Musa Asiah Integrated School (SEPAMA) Svay Khleang, Cambodia - Ismail Nasution; Sobyan Salam (PT Agung Media Publisher, 2024)
Oratory skills play a vital role in enhancing communication abilities in both academic and everyday settings. At the Musa Asiah Integrated School (SEPAMA) in Svay Khleang, Cambodia, there is a growing need to improve students' speech skills in Malay and Indonesian, languages commonly used in the school. This study aims to enhance students' oratory abilities through a structured training program focusing on speech techniques, structure, and language use. The training program involved theoretical and practical sessions, including lectures, practical exercises, and speech simulations. Junior high students at SEPAMA participated in this program, which was designed to cover aspects such as speech techniques, speech structure, and the appropriate use of Malay and Indonesian languages. Evaluations were conducted through direct observation, instructor feedback, and a final assessment of the students' speaking skills the training program significantly improved students' speech skills in both languages. Participants demonstrated noticeable progress in speech structure, fluency, and effective communication techniques. Although challenges such as vocabulary differences and nervousness were encountered, students successfully overcame these obstacles with the support provided during the training. Regular training sessions and tailored support will help sustain these improvements and enhance students' overall communication skills. This speech technique training at SEPAMA significantly improved students' public speaking abilities in both Malay and Indonesian, highlighting the importance of continuous development and support. Regular practice and supplementary materials are recommended to further strengthen students' oratory skills in these languages.